Pengaruh Penggunaan Media Gambar Untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa Kelas VII Di Madrasah Tsanawiyah Muhammadiyah 12 Palirangan - Idzi' Layyinati (STIT Muhammadiyah Paciran Lamongan, 2021)
Education is a necessity for everyone. Educational activities are activities that are very important in human life and cannot be separated from their lives. With education, human needs regarding change and development can be fulfilled. The mean score of the pre-test results was 71.73, while the mean value of the post-test results was 79.61. From these data it can be seen that the pre-test result value is lower than the post-test score, so it can be interpreted that there are differences in student learning outcomes before and after using image media in the learning process. the completeness of the pre-test result value is 46.15%, while the post-test result value is 80.76%. From this data, it can be seen that using image media can affect student learning outcomes. Then from the hypothesis testing using the Product Moment Correlation test and the Paired Sample T-test with the help of SPSS 20 software in the sig (2-tailed) section, it isknown that 0.000 <0.05 The condition is if r count is smaller than r table, then H0 is accepted. and Ha is rejected and vice versa if r count is greater than r table (r count> r table) then H0 is rejected and Ha is accepted. In fact, r count (0.977) is greater than r table (0.404). Thus H0 is rejected and Ha is accepted. As the basis for decision making in the Product Moment Correlation test and decision guidelines based on the probability value, it can be concluded that H0 is rejected and Ha is accepted. This means that image media can affect the improvement of learning outcomes in Arabic language material for class VII at MTs. Muhammadiyah 12Palirangan